Bảo tồn di tích lịch sử và giá nhà phố: Nghiên cứu điển hình tại TP. Hồ Chí Minh - Nguyen Thi Hong , Thu; Nguyen Luu Bao , Doan; Nguyen Anh, Tuan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The current study contributes to the existing scholarly and professional debate on the role and impacts of sites and landmarks designated as heritage preservation in Vietnam. Preservation proponents often contend that designated sites and landmarks can generate positive externalities; however, their arguments lack empirical support. The current study examines housing prices and their relationship with the presence of designated sites and landmarks in Ho Chi Minh City by using Hedonic models for a sample of 260 townhouses. The findings are consistent with the literature which shows the negative correlation between housing prices and distances to nearest sites and landmarks. The findings suggest important implications concerning housing transaction taxation and the community’s proactive participation in preservation policy.